The Reflection of Economic Power in Natasha Solomons' The House at Tyneford Novel - Yuni Nadziroh; Singgih Kuncara; Eka Sudirman (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
This research analyzes economic power towards the main character in The House at Tyneford Novel, written by Natasha Solomons. This research applied Dobie's economic power and Gill's characterization theory. This research used a qualitative method and Marxist approach to present the class distinction in capitalist society. This research showed two indicators of class they were bourgeoisie and proletariat. Bourgeoisie referred to Rivers Family consists of Mr. Rivers and his son Christopher Rivers, Kit. They were the owner of Tyneford House and economically privileged. Rivers’ family also has domination to controls all people who live in their houses. Meanwhile, the proletariat referred to Elise Landau, a Jewish character and also a servant in the Tyneford house whose life only depends on the employer. The proletariat were also subordination, they were powerless because they had no power to break the mode of production, and they were economically dominated.